Catalytic Hydrogenation of Acetic Acid to Acetaldehyde: Synergistic Effect of Bifunctional Co/Ce‐Fe Oxide Solid Solution Catalysts. Issue 7 (24th May 2019) - Li, Naixu; Zhang, Qi; Bibi, Rehana; Shen, Quanhao; Ngulube, Richard; Liu, Yunyi; Zhou, Jiancheng
Summary of main observation and conclusion: The large‐scale industrial production of acetic acid (HAc) from carbonylation of methanol has enabled intense research interest from direct hydrogenation of HAc to acetaldehyde (AA). Herein, a series of cerium‐iron oxide solid solution supported metallic cobalt catalysts were prepared by modified sol‐gel method and were applied in gas‐phase hydrogenation of HAc to AA. A synergistic effect between the hydrogenation metal cobalt and Ce‐Fe oxide solid solution is revealed. Specifically, oxygen vacancies provide the active sites for adsorption of HAc, while highly uniformly dispersed metallic Co adsorbs H2 and activates the reduction of HAc into AA. Moreover, the metallic Co can also assist the cyclical conversion between Fe 3+ /Fe 2+ and Ce 3+ /Ce 4+ on the surface of Ce1‐x Fex O2‐δ supports. The unique effect substantially enhances the ability of the support material to rapidly capture oxygen atoms from HAc. It is found that the catalyst of 5% Co/Ce0.8 Fe0.2 O2‐δ with the highest concentration of oxygen vacancy presents the best catalytic performance ( i.e . acetaldehyde yield reaches 49.9%) under the optimal reaction conditions ( i.e . 623 K and H2 flow rate = 10 mL/min). This work indicates that the Co/Ce‐Fe oxide solid solution catalyst can be potentially used for the selective hydrogenation from HAc to AA. The synergy between the metallic Co and Ce1‐x Fex O2‐δ revealed can be extended to the design of other composite catalysts. Abstract :